Large-Scale Analysis of Polyhydroxyalkanoate Synthases in Pseudomonas: Highly Diverse Enzymes with Potential for a Novel Class and Dissemination by Horizontal Gene Transfer - Poblete-Castro, I (Oxford University Press, 2025)
Aims To investigate the diversity, phylogenetic distribution, and structural features of polyhydroxyalkanoate (PHA) synthases (PhaCs), key enzymes for producing bioplastics, in different well-known and poorly-studied species of Pseudomonas. As Antarctic Pseudomonas spp. with unique PhaCs and PHA synthesis capabilities have been reported, we aimed to explore the PhaC dotation and classes in strains from this and other environments and the dissemination potential of the phaC genes. Methods and results We compared 859 genomes from 186 Pseudomonas species, including 33 from Antarctica. PhaC gene identification, multiple alignments, phylogenetic inference, and 3D structure prediction were applied to compare and classify the PhaCs. Most isolates encoded two class-II PhaCs, some showing additional class II and class I enzymes, especially from Antarctica, outstanding Pseudomonas frigusceleri MPC6 harboring five PhaCs, one from a potential novel class. Different PhaC subclasses were proposed based on this diversity. Despite substantive sequence variation, all the PhaCs showed a highly conserved 3D structure. Also, several phaC genes were inside putative genomic islands, phages, and plasmids, supporting their acquisition by multiple horizontal transfer routes. Conclusions To our knowledge, this is the first report investigating the PhaCs present across the Pseudomonas genus, unveiling a remarkable diversity of these enzymes and their common dissemination in mobile elements, likely contributing to the host cell fitness. Our findings underline the potential of Pseudomonas species from Antarctica and other environments and their PhaCs for producing PHAs with varying monomer compositions and properties. Future research is essential to elucidate the enzymatic properties of this underexplored PhaC diversity. © 2025 The Author(s). Published by Oxford University Press on behalf of Applied Microbiology International. All rights reserved.